Low-density lipoprotein cholesterol in a global cohort of 57, 885 statin-treated patients. (December 2016) - Gitt, Anselm K.; Lautsch, Dominik; Ferrieres, Jean; Kastelein, John; Drexel, Heinz; Horack, Martin; Brudi, Philippe; Vanneste, Brecht; Bramlage, Peter; Chazelle, Francois; Sazonov, Vasilisa; Ambegaonkar, Baishali
Abstract: Background and aims: There is an inconsistency between international guidelines on lipid-lowering treatment regarding whether to pursue LDL-C treatment targets or to focus on the intensity of treatment. While either approach is attractive, there is no recent global data on actual LDL-C values, treatment targets attained, and the intensity of treatment in statin-treated patients. We aimed to determine and compare the extent of treatment target attainment globally using standardized data collection. Methods: Analyses were based on the Dyslipidemia International Study (DYSIS), a cross-sectional study documenting statin-treated outpatients throughout 30 countries worldwide (across Europe, the Middle East, Canada, Africa, and Asia). Patients were classified as being at very high, high, or non-high cardiovascular risk based on the 2011 European Society of Cardiology (ESC)/European Atherosclerosis Society (EAS) guidelines. Results: Data were available for a total of 57, 885 patients with a median LDL-C value of 98.2 mg/dl (IQR: 76.6, 125.7 mg/dl). Overall, only 26.8% of patients were documented to have attained their risk-based target LDL-C level. Of the 76% of patients who were classified as being at very high risk, only 21.7% attained their LDL-C goal. Globally, the median distance to target was 33.0 mg/dl, ranging from 18.8 to 42.1 mg/dl across countries. We calculated that a further LDL-C reduction of just 10 mg/dl would result in an 11% increase in the proportion of very-high-risk and high-risk patients attaining their target level (9% for non-high risk patients). Conclusions: In spite of statin therapy, LDL-C values were high, with a substantial distance to target that was even more pronounced in (very) high risk patients. These results call for the optimization of existing treatment strategies and a collaborative effort to improve the impact of treatment guidance on clinical practice. Highlights: 26.8% of patients worldwide achieved the target corresponding to their risk level. Best results were found in UAE and Kuwait with 49.5% of patients reaching the target. Achievement was lowest in Germany (14.3%), the Baltics (15.9%) and Austria (15.9%). Hypertension, HF, DM and PAD were less prevalent in the target achieving group. Median LDL-C level was much lower in target reaching patients (65.0 vs 112.0 mg/dl).